The Size of the Middle Class (Observatorio Económico, 2013)
A recent World Bank study has brought to the fore the debate over how to measure or characterize the substantial improvement that certain social groups appear to beexperiencing in Latin America. Are we in fact witnessing social change in the region, with a large expansion of the so-called middle class? This debate is notforeign to Chile, since the country has posted remarkable growth rates and a significant improvement in many human development indicators over thepast 30 years. Continue reading...
Keywords: Middle class; Income mobility